A higher performance optimum design for a tri-generation system by taking the advantage of water-energy nexus. (15th February 2021) - Safari, Mina; Sohani, Ali; Sayyaadi, Hoseyn
Abstract: The effect of taking the water-energy foot-print (nexus) into account to achieve a better optimum design for a combined cooling, heating, and power (tri-generation) system is investigated here. A residential building is chosen as the case study, and multi-objective optimization is done in two conditions for different operational strategies. A condition is the 3-objective scenario in which the energy, economic, and environmental indicators are the objective functions, while in another one, which is called the 4-objective scenario, the water foot-print is also added as an objective function. According to the results, adding the water foot-print objective function leads to change in the foremost operational strategy. The best strategy in the 3-objective optimization is the following hybrid load (FHL), whereas following monthly load (FML) is found as the foremost one of the 4-objective optimization. Moreover, when the water foot-print is considered as an objective function, all the key performance criteria of the system are improved more significantly. By applying the best strategy of the 4-objective instead of the 3-objective scenario, the energy, economic, environmental, and water consumption objective functions have 12.08, 30.25, 2.03, and 25.63% higher values, respectively (goal of the optimization is maximizing all the objective functions at the same time). Additionally, the detailed investigation for the best operational strategy of the 4-objective scenario reveals that with the contribution of 54% to the total value, the prime mover has the highest share in water consumption. Highlights: Optimization provides better results when water footprint is an objective function. The best scenario changes when water consumption is added to the objectives. The optimum energy and economic objectives are improved 12.08 and 30.25%. The optimal environmental and water consumption criteria become 2.03 and 25.63% better. For the best scenario, engine has the highest share of water footprint, with 54%.